(untitled) (Journal of the College of Basic Education, 2024)
The verses of the Holy Quran are either precise which constitute the foundation on which the Quran relies, and which carry only one meaning or they are entirely unclear and may have multiple meanings. Enemies of Islam continued to stir up unrest through the centuries, relying on several matters, like the unclear verses. The aim is to cause Muslims to doubt their faith and call into question different topics that fall under Quranic sciences. Religious scholars have confronted these attacks, including Judge Zakariya Al Ansari. This research paper aims to study the unclear verses that cover some aspects of marriage, such as taking from the wife’s dowry, marrying a stepmother, marrying a stepdaughter and the wives of the Prophet (peace be upon him), being the mothers of all believers, through considering the book of " Fath al - Rahman by revealing what is ambiguous in the Quran " written by Judge Zakariya Al Ansari. The research also looks at views of the interpreters regarding these complicated verses and their efforts to defend the rules of Noble Quran.